Dynamics of soil nutrients in abandoned sheep corrals in semi-arid Mediterranean planted forests under grazing. (May 2019) - Vinograd, Arie; Zaady, Eli; Kigel, Jaime
Abstract: Traditional sheep grazing in natural and planted forests in the Mediterranean basin is based on night penning in seasonal corrals, where excreta accumulate instead of being returned to the grazed range. Lack of planning and unawareness of the long-term effect of abandoned corrals is negatively affecting the landscape and grazing value of the forests. We studied the dynamics of soil nutrients in a chronosequence of abandoned sheep corrals in planted Eucalyptus forests in two semi-arid sites in Israel. Dung decomposition was a slow process lasting 5–10 years. Soluble-N, P and K in the soil beneath the dung layer decreased gradually. Yet, 15–20 years after corral abandonment K and P were still 2 to 3 times higher than in the surrounding range, while soluble-N decreased within 10–15 years. Biomass production in the abandoned corrals was 2–3 times higher than in the grazed range up to 20 years after abandonment. Corrals act as sinks of soil nutrients that are lost to the grazed range. We propose that a balance between nutrient inputs ( i.e . atmospheric deposition, N-fixation) and outputs ( i.e. grazing and night penning) is reached in the grazed range at a low level of soil nutrients, which may constrain vegetation productivity. Highlights: Dynamics of soil nutrients was studied in a chronosequence of abandoned corrals. Seasonal corrals act as sinks of soil nutrients that are lost to the grazing range. They maintain higher N-P-K levels than the grazing range 15–20 years after abandonment. Herbaceous biomass production was still higher 20 years after corral abandonment.